Mascot Design as a Visual Icon of Janti Park Water Park - Ningrum, Ninggar Mayang; Tomo, Sri; Febriyanto, R. Arie; Abdurrozaq, Abdurrozaq (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service initiative was carried out to strengthen the visual identity of Janti Park, a water-based recreational site that previously lacked an official mascot to distinguish itself from similar destinations. The program focused on designing an icon as visual ambassador and a symbol of local pride. The implementation adopted a participatory approach through field observation, interviews with Bumdes Jaya Janti, design consultation, and promotional media application. The outcomes included the creation of a 2D mascot illustration, its application on signage boards and merchandise, and official registration under Intellectual Property Rights (IPR). The program successfully enhanced community involvement, reinforced Janti Park’s branding, and opened opportunities for creative economy activities. This project demonstrates that collaboration among academia, village governance, and local communities can produce sustainable innovations for tourism development.